Merit students encyclopedia - Friedman, Emanuel; Halsey, William Darrach, 1918- (Macmillan Educational Co ; Collier, 1982)
Encyclopedia entries are designed for students from fifth grade through high school and are written or reviewed by subject specialists
Keywords: Encyclopedias and dictionaries